2013
DOI: 10.1093/ajh/hpt076
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure After Recent Stroke: Baseline Findings From the Secondary Prevention of Small Subcortical Strokes Trial

Abstract: In this cohort with symptomatic lacunar stroke, more than half had uncontrolled hypertension at approximately 2.5 months after stroke. Regional, racial, and clinical differences should be considered to improve control and prevent recurrent stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…9 After 1 year of participation in the Abbreviations: ACEi, angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; SBP, systolic blood pressure. trial, however, approximately two-thirds were within their assigned target.…”
Section: Discussionmentioning
confidence: 99%
“…9 After 1 year of participation in the Abbreviations: ACEi, angiotensin-converting enzyme inhibitor; ARB, angiotensin receptor blocker; SBP, systolic blood pressure. trial, however, approximately two-thirds were within their assigned target.…”
Section: Discussionmentioning
confidence: 99%
“…267,273,279 In that trial, the lowest risk of stroke recurrence was seen among patients with the lowest follow-up BP levels (median, 112 mm Hg systolic and 72 mm Hg diastolic) 280 ; those with prior ICH derived the greatest benefit, and the size of the benefit was directly related to the degree of BP lowering, with no clear evidence of a lower threshold below which the benefit attenuated or even reversed, as is seen for ischemic stroke or coronary artery disease. Results of the Secondary Prevention of Small Subcortical Strokes (SPS3) study have shown that the greatest benefit of "more intensive" BP lowering is on the prevention of ICH in patients with established small-vessel stroke disease and that lowering target SBP to <130 mm Hg significantly reduced the risk of ICH (risk reduction, 60%; HR, 0.37; P=0.03), 281 which suggests that ICH patients should have their BP lowered to or beyond the targets currently recommended in other high-risk groups (<130 mm Hg systolic and 80 mm Hg diastolic in the presence of diabetes mellitus, heart failure, or chronic kidney disease). 282 Other factors, such as BP variability, the presence of obstructive sleep apnea, 283,284 obesity, and other lifestyle modifications, should also be considered despite the lack of systematic data regarding their effect on ICH recurrence.…”
Section: Bp Managementmentioning
confidence: 99%
“…In the recent Secondary Prevention of Small Subcortical Stroke (SPS3) trial, an international multisite 2 × 2 factorial design trial of two levels of SBP control and two regimens of antiplatelet therapy in which both normotensive and hypertensive patients with recent lacunar stroke were randomized, non-Hispanic black participants were more likely to report a history of hypertension prior to stroke, have uncontrolled hypertension at time of enrollment, and be taking more antihypertensive medications than the other racialethnic groups [ 51 ]. Reasons for uncontrolled treated hypertension are multifactorial, and some are similar across race-ethnic groups, i.e., age, medication nonadherence, not receiving regular medical care, treatment-resistant hypertension, and lack of healthy behaviors such as physical activity, etc., but persons of African ancestry are more likely to have treatment-resistant hypertension and specifi c associated pathophysiology of hypertension, i.e., low-renin hypertension, etc., that require targeted evaluation and management [ 52 , 53 ].…”
Section: Black-white Disparities In the Impact Of Stroke Risk Factorsmentioning
confidence: 99%